(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines the key role of technology in the modern educational process. It analyzes the main aspects of technology’s influence on learning, including their contribution to information accessibility, the development of critical thinking, and interaction between students and teachers. The positive and negative sides of technological integration into educational systems are discussed, as well as the impact of technology on various levels of education. In conclusion, the necessity of a balanced approach to the use of technology in the educational process is emphasized.